Problems and countermeasures of transformation from financial accounting to management accounting in the era of big data explored - Yelong Jin; Qiqi Li (International Scientific Technical and Economic Research, 2025)
The digital era is an era of opportunities and challenges, in the digital wave of enterprises need to adapt to the development of the times and constantly improve their own shortcomings. Due to the continuous innovation of technology, the scope and content of the traditional financial work is constantly compressed, the traditional financial accounting has been unable to meet the needs of the current stage of development of enterprises, must be transformed to management accounting. This paper analyses the current financial accounting to management accounting transition problems, and puts forward corresponding countermeasures, hoping to bring different thinking for traditional accountants, not only to help accountants successfully complete their career transition, but also for the development of enterprise decision-making to provide effective analysis and support.